On strictly weak mixing C*-dynamical systems and a weighted ergodic theorem - Mukhamedov, Farrukh (Akademiai Kiado, 2010)
We prove that unique ergodicity of tensor product of a C*-dynamical system implies its strictly weak mixing. By means of this result a uniform weighted ergodic theorem with respect to S-Besicovitch sequences for strictly weak mixing dynamical systems is proved.Moreover, we provide certain examples of strictly weak mixing dynamical systems.